Does inspiratory muscle training provide additional benefits during pulmonary rehabilitation in people with interstitial lung disease? A randomized control trial. (4th March 2023) - Zaki, Saima; Moiz, Jamal Ali; Mujaddadi, Aqsa; Ali, Mir Shad; Talwar, Deepak
ABSTRACT: Background: Interstitial lung disease (ILD) encompasses a diverse group of chronic lung conditions which is often characterized by inspiratory muscle weakness (IMW). Despite the potential importance of inspiratory muscle dysfunction in ILD, the effect of inspiratory muscle training (IMT) added to pulmonary rehabilitation (PR) in ILD largely remains unknown. Objective: The primary objective of the present study was to evaluate the benefits of IMT added to PR on inspiratory muscle strength and secondary objectives were to assess its effects on functional capacity, health-related quality of life (HRQoL), pulmonary function test (PFT) and dyspnea in ILD along with IMW. Methods: Fifty-one participants were randomly allocated into two groups; PR + IMT (n = 26) or PR alone (n = 25). The primary outcome [maximal inspiratory pressure (PImax )] and secondary outcomes [6-min walk distance (6MWD), St. George's Respiratory Questionnaire (SGRQ), PFT and modified Medical Research Council dyspnea scale (mMRC)] were evaluated before and after the 8-weeks intervention. Independent t-test or Mann Whitney-U test was applied for between-group comparisons while for within-group comparison Wilcoxon's Sign Rank test or paired t test was performed. Results: At the end of 8 weeks exercise intervention inspiratory muscle strength (PImax + 11.10 cm H2 O, p < .001), functional capacity (6MWD, + 47.90 m, p = .001), HRQoL (SGRQ-total – 4 points, p = .038) and dyspnea (mMRC dyspnea scale, −1.27, p < .001) improved significantly in PR+IMT group alone. Conclusion: Inclusion of IMT to PR may have superior benefits as compared to PR alone in ILD accompanied with IMW.